Genetic and phenotypic assessment of the antimicrobial activity of three potential probiotic lactobacilli against human enteropathogenic bacteria - Kiousi, Despoina Eugenia; Efstathiou, Christos; Tzampazlis, Vasilis; Plessas, Stavros; Panopoulou, Maria; Koffa, Maria; Galanis, Alex (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Lactobacilli are avid producers of antimicrobial compounds responsible for their adaptation and survival in microbe-rich matrices. The bactericidal or bacteriostatic ability of lactic acid bacteria (LAB) can be exploited for the identification of novel antimicrobial compounds to be incorporated in functional foodstuffs or pharmaceutical supplements. In this study, the antimicrobial and antibiofilm properties of Lactiplantibacillus pentosus L33, Lactiplantibacillus plantarum L125 and Lacticaseibacillus paracasei SP5, previously isolated form fermented products, were examined, against clinical isolates of Staphylococcus aureus, Salmonella enterica subsp. enterica serovar Enteritidis and Escherichia coli. Methods The ability of viable cells to inhibit pathogen colonization on HT-29 cell monolayers, as well as their co-aggregation capacity, were examined utilizing the competitive exclusion assay. The antimicrobial activity of cell-free culture supernatants (CFCS) was determined against planktonic cells and biofilms, using microbiological assays, confocal microscopy, and gene expression analysis of biofilm formation-related genes. Furthermore, in vitro analysis was supplemented with in silico prediction of bacteriocin clusters and of other loci involved in antimicrobial activity. Results The three lactobacilli were able to limit the viability of planktonic cells of S. aureus and E. coli in suspension. Greater inhibition of biofilm formation was recorded after co-incubation of S. enterica with the CFCS of Lc. paracasei SP5. Predictions based on sequence revealed the ability of strains to produce single or two-peptide Class II bacteriocins, presenting sequence and structural conservation with functional bacteriocins. Discussion The efficiency of the potentially probiotic bacteria to elicit antimicrobial effects presented a strain- and pathogen-specific pattern. Future studies, utilizing multi-omic approaches, will focus on the structural and functional characterization of molecules involved in the recorded phenotypes.